Management and Clinical Outcome of Posterior Reversible Encephalopathy Syndrome in Pediatric Oncologic/Hematologic Diseases: A PRES Subgroup Analysis With a Large Sample Size - Hun, Marady; Xie, Min; She, Zhou; Abdirahman, Amin S.; Li, Cuifang; Wu, Feifeng; Luo, Senlin; Han, Phanna; Phorn, Rithea; Wu, Pan; Luo, Haiyan; Chen, Keke; et al. (Frontiers in Pediatrics, 2021)
This study investigated the management and clinical outcomes along with associated factors of posterior reversible encephalopathy syndrome (PRES) in childhood hematologic/oncologic diseases. We present data from children with hematologic/oncologic diseases who developed PRES after treatment of the primary disease with chemotherapy and hematopoietic stem cell transplantation (HSCT) at 3 medical centers in Changsha, China from 2015 to 2020, and review all previously reported cases with the aim of determining whether this neurologic manifestation affects the disease prognosis. In the clinical cohort of 58 PRES patients, hypertension (pooled odds ratio [OR]=4.941, 95% confidence interval [CI]: 1.390, 17.570; P=0.001) and blood transfusion (OR=14.259, 95% CI: 3.273, 62.131; P=0.001) were significantly associated with PRES. Elevated platelet (OR=0.988, 95% CI: 0.982, 0.995; P<0.001), hemoglobin (OR=0.924, 95% CI: 0.890, 0.995; P<0.001), and blood sodium (OR=0.905, 95% CI: 0.860, 0.953; P<0.001), potassium (OR=0.599, 95% CI: 0.360, 0.995; P=0.048), and magnesium (OR=0.093, 95% CI: 0.016, 0.539; P=0.008) were protective factors against PRES. Data for 440 pediatric PRES patients with hematologic/oncologic diseases in 21 articles retrieved from PubMed, Web of Science, and Embase databases and the 20 PRES patients from our study were analyzed. The median age at presentation was 7.9 years. The most common primary diagnosis was leukemia (62.3%), followed by solid tumor (7.7%) and lymphoma (7.5%). Most patients (65.0%) received chemotherapy, including non-induction (55.2%) and induction (44.8%) regimens; and 86.5% used corticosteroids before the onset of PRES. Although 21.0% of patients died during follow-up, in most cases (93.2%) this was not attributable to PRES but to severe infection 27.3%), underlying disease (26.1%), graft-versus-host disease (14.8%), multiple organ dysfunction syndrome (8.0%), and respiratory failure (3.4%). PRES was more common with HSCT compared to chemotherapy and had a nearly 2 times higher mortality rate in patients with oncologic/hematologic diseases than in those with other types of disease. Monitoring neurologic signs and symptoms in the former group is therefore critical for ensuring good clinical outcomes following treatment of the primary malignancy.